Pengaruh Warna Perangkap Feromon terhadap Hasil Tangkapan Imago Oryctes rhinoceros di Perkebunan Kelapa Sawit - Idum Satia Santi; Bambang Sumaryo; F. X. Wagiman (Jurnal Perlindungan Tanaman Indonesia, 2008)
The effectiveness of a synthetic-pheromone trap with active ingredient of ethyl-4-methyloctanoate in catching adults of Oryctes rhinoceros was believed to be influenced by the trap color. A RCBD trial with single factor and three block replicates was conducted during September to October 2008 at Oil-Palm-Trial Station at PTPN III, Labuhan Batu District, North-Sumatera Province. The single factor was trap color i.e. orange, green, white, blue, red, yellow, and pink. Results showed that total numbers and sex ratios of collected O. rhinoceros adults were not significantly influenced by the trap color. The total numbers of collected O. rhinoceros adult during 30 days on color of orange, green, white, blue, red, yellow, and pink were 136, 177, 126, 155, 129, 114, and 113 individuals with sex ratios ♂/♀ 0.47, 0.52, 0.62, 0.50, 0.60, 0.49, and 0.54, respectively. The synthetic pheromone significantly attracted more O. rhinoceros female (65%) rather than the male one (35%).